1990
DOI: 10.1111/j.1365-2230.1990.tb02107.x
|View full text |Cite
|
Sign up to set email alerts
|

Hairy leucoplakia-a clinical, histopathological and ultrastructural study in 33 patients

Abstract: Thirty-three cases of hairy leucoplakia (HL) in HIV-positive patients were studied. The most frequent clinical presentation was the development of corrugated plaques on the lateral sides of the tongue without spiculations on the surface. In all biopsies, herpetic-type viral inclusions were found. In 12 out of 14 cases in whom an electromicroscopic study was carried out, only viral particles of the herpes group were found. Human papillomavirus (HPV) was not demonstrated, although by means of immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Previously, the frequency of OHL in HIV-positive individuals was reported to increase as the CD4 count falls (Aragues et al, 1990;Feigal et al, 1991;Glick et al, 1994;Husak et al, 1996;Lifson et al, 1994). However, in this study, the mean CD4 count among the OHL group was 388 cells l −1 , which was not significantly different from that of the HIV-positive group without OHL (371 cells l −1 ).…”
Section: Discussioncontrasting
confidence: 86%
“…Previously, the frequency of OHL in HIV-positive individuals was reported to increase as the CD4 count falls (Aragues et al, 1990;Feigal et al, 1991;Glick et al, 1994;Husak et al, 1996;Lifson et al, 1994). However, in this study, the mean CD4 count among the OHL group was 388 cells l −1 , which was not significantly different from that of the HIV-positive group without OHL (371 cells l −1 ).…”
Section: Discussioncontrasting
confidence: 86%
“…[30][31][32][33] Further studies in the HIV-positive individual showed that not only was the lesion associated with decreased blood CD4 ϩ T cells, but development of the lesion was also associated with shortened survival time. [34][35][36][37] The etiologic agent is Epstein Barr virus (EBV), a virus that is also detectable in the oral mucosa of HIV-negative individuals. 31,38 HIV-positive patients demonstrate higher rates of detectable EBV-DNA in oral epithelial cells than HIV-negative individuals, (42.1% compared to 16.6%, respectively), however, HIV-negative immune suppressed renal transplant patients demonstrate higher rates of detectable EBV-DNA than HIV-positive patients (65% compared to 42.1%, respectively).…”
Section: Epidemiology Of Oral Lesions In the Hiv-positive Patientmentioning
confidence: 99%
“…In addition to clinically manifest Candida infection , virally induced lesions represent the most common oral manifestation in patients with HIV infection . None of these oral diseases are pathognomonic for HIV infection per se, and may also be seen in other types of immunosuppressive conditions [8,30,31].However, HL has been found to be much more frequently associated with HIV seropositivity than other immunosuppressive conditions , such as immunosuppressive drug treatment for renal transplants and autoimmune diseases such as Sjogren's syndrome and systemic lupus erythematosus, in the patients studied.…”
Section: Discussionmentioning
confidence: 86%
“…The koilocytoid cells occur in clusters [4,6]. Cowdry type inclusion bodiesm, which are typical of cells infected with herpesvirus, have been reported in HL [5,8]. Greatly reduced numbers or absence of Langerhans cells are a characteristic feature of HL and this has been considered an important factor in its pathogenesis [9].…”
Section: Introductionmentioning
confidence: 99%